The drop [compact disc, unabridged] : a novel - Connelly, Michael, 1956- (Connelly, Michael, 1956- Harry Bosch series, 2011)
LAPD detective Harry Bosch simultaneously investigates a killer who has been operating undetected for thirty years and a political conspiracy that has its origins in his police department.